Aristotle vs. Plato: The classical origins of capitalist & socialist political economies - Theocharis Grigoriadis (Scottish Journal of Political Economy, 2022)
Competing definitions of justice in Plato's Republic and Aristotle's Politics indicate the existence of two distinct economic systems with different priorities. The three-class society of the Platonic economy (guardians, auxiliaries, producers) gives rise to guardians who by virtue are expected to enforce output targets on producers directly or through auxiliaries. The three-class society of the Aristotelian economy (rich, middle, poor) facilitates the emergence of different ruling coalitions and compensates the efficiency losses of central planning with political gains derived from representative governance. In the Aristotelian economy, the middle class is better off than in the Platonic economy (auxiliaries), because a just society (polity) is achieved under its coalition with the rich. I argue that the equilibrium solutions of the Platonic and Aristotelian economic systems provide analytical insights on the origins of capitalist and socialist political economies.
Keywords: 330; Aristotle; central planning; economic systems; market mechanism; Plato; political regimes